1990
DOI: 10.1111/j.1432-1033.1990.tb19433.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent folding of individual components in hybrid proteins

Abstract: Inactivation of the Escherichia coli repressor protein, LexA, takes place through a cleavage reaction which hydrolyzes the Ala84-Gly85 peptide bond near the center of the molecule. The mechanism of cleavage has previously been shown to be an intramolecular reaction stimulated in vitro by elevated pH or by the addition of activated RecA protein. The entire self-cleavage activity of LexA has been found to lie within a 135-residue tryptic fragment extending from Leu68 to the end of the protein at Leu202. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…In addition, the SOS induction assays indicated that the putative LexA552 protein would not suffer autoproteolytic cleavage by RecA coprotease, even though it contains the amino acids apparently involved in this process (13,36). This agrees with the fact that only protein fusions containing the entire 135 carboxy-terminal residues of LexA of E. coli are self-cleavable (35).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, the SOS induction assays indicated that the putative LexA552 protein would not suffer autoproteolytic cleavage by RecA coprotease, even though it contains the amino acids apparently involved in this process (13,36). This agrees with the fact that only protein fusions containing the entire 135 carboxy-terminal residues of LexA of E. coli are self-cleavable (35).…”
Section: Discussionsupporting
confidence: 71%
“…On the basis of its sequence, this transcript should encode a fusion protein of about 29 kDa, containing the first 184 amino acids encoded by lexA and 82 amino acids encoded by the HindIII fragment of Tn5. Therefore, since this LexA552 protein would lack the last 18 amino acids of the C-terminal domain, its normal DNAbinding activity would be inhibited and it would be unable to cleave itself (32,35).…”
Section: Resultsmentioning
confidence: 99%
“…Domains have been often observed to fold independently of the remainder of polypeptide. A few of many examples include lysozyme (Radford et al, 1992), thermolysin (Corbett & Roche, 1986), aspartate transcarbamylase (Maley & Davidson, 1988), lexA repressor (Slilaty et al, 1990), exotoxin (Brinkmann et al, 1992), and Tu elongation factor (Nock et al, 1995). Though it is not always clear that single domains (and domain-segments) fold independently, ends of such segments certainly delineate transition from one structural unit to another.…”
Section: Domain Foldingmentioning
confidence: 99%